2017
DOI: 10.5327/z259453942017edit273
|View full text |Cite
|
Sign up to set email alerts
|

Why is breast cancer early detection important?

Abstract: EDITORIALO n June 15 of the current year, the Brazilian Society of Mastology -Rio de Janeiro Region (SBM/RJ) promoted a discussion on public health policies in breast cancer at the VII International Symposium on Mastology -Rio (SIM Rio). There was a seminar addressing the barriers and strategies for the implementation of the guidelines for the early detection of breast cancer in Brazil.Strategies for the early detection of breast cancer and rapid access to treatment were discussed. Such factors are essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…PNP is aimed at providing timely diagnosis and treatment our complex and fragmented SUS. It has the potential to offer dignity to health system users, eliminating barriers and bureaucracies with attention to the human being and not the disease itself, transforming the disease regulatory system into a patient follow-up system [14]. PN was responsible for the compliance of the "60-Day Law" in 52% of the cases, not reaching the project's target of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…PNP is aimed at providing timely diagnosis and treatment our complex and fragmented SUS. It has the potential to offer dignity to health system users, eliminating barriers and bureaucracies with attention to the human being and not the disease itself, transforming the disease regulatory system into a patient follow-up system [14]. PN was responsible for the compliance of the "60-Day Law" in 52% of the cases, not reaching the project's target of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The family clinic needs to address the lifestyle change of the target population due to the high incidence of comorbidities, physical inactivity and obesity, known risk factors for breast cancer. Because of the high incidence of family risk for breast cancer in this population, genetic counseling and specific management for the high-risk population need to be further explored 25 . It was observed that patients and health professionals from the Andaraí family clinic have difficulty in identifying risk factors and specific actions related to breast health.…”
Section: Employmentmentioning
confidence: 99%
“…It was observed that patients and health professionals from the Andaraí family clinic have difficulty in identifying risk factors and specific actions related to breast health. In practice, the engagement of breast cancer specialists in primary health care is necessary to optimize the training of health professionals and patients 25 .…”
Section: Employmentmentioning
confidence: 99%
“…The training of primary care health professionals, as a tool to improve patient flow to the breast health care line, should be supported by managers and involve breast cancer specialists 26…”
Section: Health Professionalsmentioning
confidence: 99%
“…(Fiocruz), found that the highest level of governance and increased health coverage in primary care in Brazilian municipalities are associated with reduced mortality 26 . The family health strategy can be a good context for initiating organized breast cancer screening in Brazil, contributing to the strengthening of the guidelines.…”
Section: Motivation To Changementioning
confidence: 99%